INVARIANT SYSTEM OF THE STEAM-DRUM BOILER FEED AUTOMATIC REGULATION - G. T. Kulakov; A. N. Kukhorenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2015)
The choice of the controlling system structure, law of control, and optimal parameters for the regulator dynamic settings exercise, under principal influences, substantial effect on quality of the transient processes of water-level change in the shell of the boiler. At the present moment, techniques of design by analysis for the optimal regulating systems allow improving quality of the transient processes. Applying the method of structural-parametrical optimization and the invariance theory render it possible to significantly improve quality of the boiler-shell water level maintaining by means of changing the system structure and optimizing the feed automatic-control system dynamic settings. However, this becomes attainable at the expense of increasing the control-action maximum magnitude with the feeding water rate. At the same time, the indicator of the latter should be less than the control-action value of the typical threeelement control of the feed-regulation system as this directly links to the boiler equipment safety, the drum metal and the feed-water economizer longevity. For removal of this shortcoming, the paper proposes to form in parallel to the real inertial region of the controlled member its dynamic simulation which allows separating the equivalent external disturbance without having to measure it. And to limit the compensation device output to the control-action value of the typical three-element control system of the automatic feed-regulation. This leads to the maximum control-action magnitude decrease, besides, the external-disturbances execution time remains unchanged. Altogether, under all the influences, the authors report of receiving substantial improvement of regulation quality as compared with the typical three-element automatic feed-regulation system